Pengembangan Lembar Kerja Mahasiswa Mata Kuliah Gelombang dan Bunyi Berbasis Niteni, Nirokke, Nambahi - Hidayati Hidayati; Daimul Khasanah (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to develop, test the feasibility and measure student responses to Student Worksheets in the wave and sound course based 3N (Niteni, Nirokke, Nambahi). The research method used is research and development using the Borg and Gall model which consists of five steps, namely exploration studies, initial product development, expert validation and product revisions, limited trials and product revisions, main trials and revisions to the final product. The instrument used was a validation questionnaire for material experts and media experts as well as a student response questionnaire. Data analysis techniques used qualitative and quantitative data. The results of the study were 3N-based sound and wave LKM which were valid with very good criteria and very suitable for use, practical, interesting, more able to motivate and help students understand the concept. The average score of the validation results from material experts and media experts was 3.52 or 88.08%, in the very good category and the student response was 3.65 or 91.4% in the very good category.